2022
DOI: 10.14421/ahwal.2021.14201
|View full text |Cite
|
Sign up to set email alerts
|

HUKUM PERKAWINAN ISLAM DI RUANG DIGITAL: Bias Gender dalam Wacana Hukum Perkawinan di Instagram

Abstract: This study departs from the widespread social media content created and distributed by conservative groups. One of the topics frequently addressed by this group is family law discourse, which includes instructions for selecting a mate, marriage advice, the fulfillment of rights and obligations in the family, and other topics related to relationships in domestic life. Using Foucault's discourse analysis approach, this article investigates the dominant narratives that portray family law. The data for this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…With the growth of social media and technological disruption, media accessibility has become more extensive, and the media has become the primary means of knowledge transformation. One example is the construction of discourse about marriage, which becomes public consumption through social media (Handayani, 2022). In this article, we will further discuss how multimedia can be used to reconstruct Islamic family law.…”
Section: Introductionmentioning
confidence: 99%
“…With the growth of social media and technological disruption, media accessibility has become more extensive, and the media has become the primary means of knowledge transformation. One example is the construction of discourse about marriage, which becomes public consumption through social media (Handayani, 2022). In this article, we will further discuss how multimedia can be used to reconstruct Islamic family law.…”
Section: Introductionmentioning
confidence: 99%
“…The community massively follows Instagram accounts about husband-and-wife relationships in marriage to learn how to be a good husband and wife. Yulmitra Handayani (2021) warns that these accounts can be problematic if the discourse ignores moderate logic and Islam's respectful and compassionate norms. 6 The accounts published still produce advantageous and negative perceptions in society, especially among Instagram media activists.…”
Section: Introductionmentioning
confidence: 99%
“…From these issues, the author's academic concern developed from Instagram posts. Yulmitra Handayani's (2021) research found a gender bias in Instagram marriage law content, which marginalises women and positions traditional fiqh over contemporary fiqh advancements. 9 However, many studies support this content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation